A50 MODULATION OF GOBLET CELL ACTIVITY DURING GIARDIA DUODENALIS INFECTION: A ROLE FOR PAR2. (4th March 2021) - Fekete, E; Amat, C B; Allain, T; Hollenberg, M; Mihara, K; Chadee, K; Buret, A
Abstract: Background: Giardia duodenalis has been shown to alter the structure of the intestinal mucus layers during infection via obscure mechanisms. We hypothesize that goblet cell activity may be disrupted in part due to proteolytic activation of protease-activated receptor 2 (PAR2) by Giardia proteases, resulting in disruption of mucus production and secretion by intestinal goblet cells. Aims: Characterize alterations in goblet cell activity during Giardia infection, focusing on the roles of Giardia protease activity and PAR2. Methods: Chinese hamster ovary cells transfected with nano-luciferase tagged PAR2 were incubated with Giardia NF or GSM trophozoites. Cleavage within the activation domain results in release of enzymes into the supernatant. Luminescence in the supernatant was measured as an indication of PAR cleavage by Giardia . LS174T, a human colonic mucus-producing cell line, was infected with Giardia trophozoites (isolates NF, WB, S2, and GSM). Prior to infection, trophozoites were treated with E64, a broad-spectrum cysteine protease inhibitor, and LS174T were treated with a PAR2 antagonist, a calcium chelator, or an ERK1/2 inhibitor. Quantitative PCR (qPCR) was performed for the MUC2 mucin gene. Wild-type (WT) and PAR2 knockout (KO) mice were infected with Giardia . Colonic mucus was stained using fluorescein-coupled wheat-germ agglutinin (WGA), and qPCR was performed for Muc2 and Muc5ac. Results: Giardia trophozoites cleaved PAR2 within the N-terminal activation domain in a cysteine protease-dependent manner. Cleavage was isolate dependent, with isolates that show higher protease activity cleaving at a higher rate. High protease activity Giardia isolates increased MUC2 gene expression in LS714T. This increase was attenuated by inhibition of Giardia cysteine protease activity, and by antagonism of PAR2, inhibition of calcium release, or inhibition of ERK1/2 activity in LS174T cells. Both Muc2 and Muc5ac expression were upregulated in the colons of WT mice in response to Giardia infection, while in the jejunum Muc2 expression decreased and Muc5ac expression increased. In KO, no changes in gene expression were seen in the colon in response to Giardia infection, while in the jejunum, Muc2 expression was unchanged and Muc5ac expression decreased. Both WT infected and KO noninfected mice showed thinning of the colonic mucus layer compared to WT controls. There was some recovery in thickness in KO infected mice. Conclusions: PAR2 plays a significant role in the regulation of mucin gene expression in mice and in a human colonic cell line. Results suggest that Giardia cysteine proteases cleave and activate PAR2, leading to calcium release and activation of the MAPK pathway in goblet cells, ultimately leading to altered mucin gene expression. Findings identify a novel regulatory pathway for mucus production by intestinal goblet cells. Funding Agencies: CAG, CCC